Who might be affected by crashes? Identifying areas susceptible to crash injury risk and their major contributing factors. Issue 2 (2nd January 2019) - Kocatepe, Ayberk; Ulak, Mehmet Baran; Ozguven, Eren Erman; Horner, Mark W.
Abstract : The growth of metropolitan regions in the U.S. leads to transportation safety issues related to roadway crashes that imperil personal well-being. Previous studies have investigated the environmental, traffic, roadway, and human related factors that influence the frequency and severity of crashes, and focused on the spatial distribution of roadway crashes. However, unfavourable health and safety consequences of crashes for different demographic locations and socioeconomic units have not been fully understood from an aggregate perspective. To achieve this understanding, our paper proposes a new concept called crash injury risk susceptibility (CRIS) and a novel two-step approach with the following components: (1) a GIS-based spatial analysis to discover the census units that are susceptible to the risk imposed by crashes and their severities, and (2) a statistical investigation to identify various elements that are associated with this risk. The analysis is carried out in the Tampa Bay region of Florida, U.S. Findings illustrate that some areas within Tampa Bay region face an elevated susceptibility to crash injury risk. As such, this study contributes to discourse on traffic safety and social sustainability, which helps enhance overall public welfare.